SEMANTIC CHARACTERISTICS OF FRUIT-RELATED WORDS IN ENGLISH, FRENCH AND UZBEK LANGUAGES (Journal of Pharmaceutical Negative Results, 2022)
Nowadays, linguistic study of various words which are related to the different kinds of branches is growing dramatically and I think it is absolutely attention-grabbing topic for everyone, particularly for students who study linguistics as their major field. While studying the linguistic features of the words which are related to divergent topics we can learn a lot of brand-new and spellbinding things and it, in turn, affects our cognitive ability tremendously. This article is devoted to study the semantic characteristics of fruit-related words and in my opinion, it gives you some valuable information.